PENGARUH MOTIVASI KERJA, KEPEMIMPINAN, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. INDUSTRI JAMU DAN FARMASI SIDO MUNCUL SEMARANG - Yuyun Eko Nurcahyati, 10.05.51.0037; Muhaimin, Muhaimin (Students Journal of Economic and Management, 2014)
This study analyzed the effect of Work Motivation, Leadership, and Organizational Culture on Employee Performance. Object of study in this research his PT. Industri Jamu dan Farmasi Sido Muncul Semararang. Sampling technique in this study is the use âPurposive Samplingâamounted to 88 respondents in the sample with the method of data collection using questionnaire (questionnaire) by the wayÂ  propagate by spreading list statement to the respondents in order to obta in information. The purpose of this study was to determine the effect of Work Motivation, Leadership, and Organizational Culture on Employee Performance. The data collected were analyzed using factor analysis to test the validity of the statement it ems, Cronbach alpha formula to test the reliability of the instrument, regression analysis, to test the influence of each partial in dependent variables we retested by regression analysis. The results of the research are : (1) Work Motivation has a positive and significant impact on employee performance. (2) Leadership has a positive and significant impact on employee performance. (3) Organizational Culture has a positive and significant impact on employee performance.Keywords: work motivation, leadership, organizational culture, and employee performance